Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio are useful markers of inflammation in polycystic ovary syndrome? - Vedavathi V; Veerabhadra Goud GK; Sudha V Patil; Rajeev Gandham (Asian Journal of Medical Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous metabolic disorder characterized by hyperinsulinemia, abnormal lipid levels, altered hormonal milieu such as elevated androgen levels, and chronic anovulation. PCOS is one of the important reasons for infertility. PCOS is the most common cause of irregular menstruation with diverse clinical manifestations affecting women of reproductive age. Aims and Objectives: The present study aimed to examine systemic inflammatory markers that can be detected in complete blood count, such as neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR), in patients with PCOS and to compare them with healthy women. Materials and Methods: This case–control study was conducted in the Department of Obstetrics and Gynecology, Akash Institute of Medical Sciences and Research Centre, Devanahalli, Bengaluru, Karnataka. After following the inclusion and exclusion criteria, a total of 160 subjects were included. Among them, 80 were PCOS patients as cases and 80 were healthy women as controls. A detailed clinical and gynecological history was obtained from all subjects. Women presenting gynecology OPD in the group of 15–45 years with irregular menstrual cycles were included in the study. The diagnosis of PCOS was done according to the Rotterdam criteria, diagnosis of PCOS requires the presence of at least two of the following three symptoms: (1) oligomenorrhea/polymenorrhea; (2) biochemical hyperandrogenism (Ferriman–Gallwey scores of ≥8) or the presence of clinical hyperandrogenism; and (3) detection of polycystic ovaries in an ultrasonographic examination (≥12 follicles, 2–10 mm in size). Under aseptic conditions, venous blood samples were collected from all the subjects to assess the hormones such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), inflammatory markers, white blood cells, neutrophils (N), lymphocytes (L), and platelets. NLR and PLR were calculated. Lipid profiles were obtained in the fasting state. Results: In the present study, BMI 24.5±4.1 kg/m2, total cholesterol 160.1±24.2 mg/dL, triglyceride 99.1±28.1 mg/dL, LDLC 99.1±25.1 mg/dL, LH 8.4±3.8 mIU/mL, LH/FSH ratio 1.2±0.91, lymphocytes 16.30±4.69, NLR 5.73±1.91, and PLR 17.01±7.13 were significantly increased in PCOS cases and HDLC 39.7±6.2 mg/dL and FSH 6.1±1.1 mIU/mL were decreased in PCOS cases compared to healthy controls. Conclusion: The study concludes that increased inflammatory markers such as NLR and PLR in PCOS cases compared to the age-matched individuals in the control group, suggesting the presence of chronic low-grade inflammation in PCOS cases of early reproductive age.